Sistem Pendukung Keputusan Pemilihan Pelanggan Terbaik Menggunakan Metode Multi-Objective Optimization on the basis of Ratio Analysis dan Pembobotan Entropy - Ardianto, Maygi; Rusliyawati, Rusliyawati (Forum Kerjasama Pendidikan Tinggi (FKPT), 2024)
Problems in selecting the best customers often include the challenge of determining the right criteria for evaluation. Other issues include misinterpretation of data or a tendency to prioritize just one criterion without considering the holistic impact on the customer relationship. The best customers also tend to have higher lifetime value, so focusing on them can increase customer revenue and loyalty. Creating a comprehensive and structured evaluation system and ensuring the availability of accurate data is key to addressing these issues and optimizing the best customer selection strategy for the company's long-term success. The application of SPK in selecting the best customers in this study uses 10 existing regular customer data, as well as utilizing the MOORA method and entropy weighting which provides an objective, efficient, and accurate tool for companies in identifying the best customers based on various relevant criteria. By using the MOORA method, the system will effectively evaluate and compare customer alternatives, while entropy weighting will ensure that the criteria weights are objectively determined based on existing data, reducing subjectivity and increasing the reliability of results. This research is expected to make a significant contribution to improving the quality of decision-making and the company's business strategy. The ranking results by applying the entropy and MOORA weighting methods showed that the first best customer with a final score of 0.467 was obtained with the name of Yadi's customer, the second best customer with a final score of 0.427 was obtained with the name of Yanah's customer, and the third best customer with a final score of 0.373 was obtained with the name of Iwan's customer.